2015
DOI: 10.1177/0309364614535621
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of soleus Hoffmann reflex by ankle–foot orthosis application in healthy volunteers

Abstract: The putative neuromodulatory effect on motor control may support the application of such ankle-foot orthoses in, for example, drop foot. Furthermore, the objective assessment of a neurophysiological mode of action of orthoses by Hoffmann reflex recordings might be an appropriate primary outcome parameter in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The generally given explanation is that HS boots or external ankle supports provide additional tactile information around the ankle and the lower part of the leg, which improves somatosensation and postural stability, with a main influence in the frontal plane. Larsen et al (2015) showed that the increased cutaneous afference information provided by the application of an ankle foot orthosis could depress the soleus H reflex and facilitate the motor function of the tibialis anterior muscle. Cordova and Ingersoll (2003) reported concordant findings while observing greater stretch reflex amplitude of the peroneus longus muscle after acute ankle brace application.…”
Section: Unstable Postural Tasksmentioning
confidence: 99%
“…The generally given explanation is that HS boots or external ankle supports provide additional tactile information around the ankle and the lower part of the leg, which improves somatosensation and postural stability, with a main influence in the frontal plane. Larsen et al (2015) showed that the increased cutaneous afference information provided by the application of an ankle foot orthosis could depress the soleus H reflex and facilitate the motor function of the tibialis anterior muscle. Cordova and Ingersoll (2003) reported concordant findings while observing greater stretch reflex amplitude of the peroneus longus muscle after acute ankle brace application.…”
Section: Unstable Postural Tasksmentioning
confidence: 99%
“…However, the energy cost during gait is improved by wearing an orthosis [ 2 ]. Furthermore, orthosis may change the sensory input and cause a change in the H-reflex and Hoffmann reflex; however, the results of these reports are inconsistent [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the energy cost during gait is improved by wearing an orthosis [2]. Furthermore, orthosis may change the sensory input and cause a change in the H-reflex and Hoffmann reflex; however, the results of these reports are inconsistent [3,4]. Specifically, previous studies in healthy adults have reported the effect of an orthosis on biomechanics during gait.…”
Section: Introductionmentioning
confidence: 99%